Role of Endoplasmic Reticulum Stress-Autophagy Axis in Severe Burn-Induced Intestinal Tight Junction Barrier Dysfunction in Mice - Huang, Yalan; Wang, Yu; Feng, Yanhai; Wang, Pei; He, Xiaochong; Ren, Hui; Wang, Fengjun (Frontiers in Physiology, 2019)
Severe burn injury induces intestinal barrier dysfunction, however, the underlying mechanisms remains elusive. Our previous studies have shown that the intestinal epithelial tight junction (TJ) barrier dysfunction is associated with both endoplasmic reticulum (ER) stress and autophagy in severely burned mice, but the precise role of ER stress and autophagy in the burned-induced intestinal TJ barrier dysfunction needs to be determined. In this study, female C57/BL6 mice were assigned randomly to either sham burn or 30% total body surface area (TBSA) full thickness burn. The effects of ER stress and autophagy on intestinal epithelial TJ barrier were validated by inducing or inhibiting both ER stress and autophagy in mice treated with sham burn or burn injury. The intestinal permeability, expression and localization of TJ proteins, ER stress and autophagy were assessed by physiological, morphological and biochemical analyses. The results showed that inducing ER stress with tunicamycin or thapsigargin caused the activation of autophagy, the increase of intestinal permeability, as well as the reduction and reorganization of TJ proteins in the sham-burned mice, and aggravated the burn-induced activation of autophagy, increase of intestinal permeability as well as the reduction and reorganizaion of TJ proteins. In contrast, inhibiting ER stress with 4-phenylbutyrate alleviated the burn-induced activation of autophagy, increase of intestinal permeability as well as the reduction and reorganizaion of TJ proteins. In addition, inducing autophagy with rapamycin resulted in the increase of intestinal permeability, as well as the reduction and reorganization of TJ proteins in the sham-burned mice, and aggravated the burn-induced increase of intestinal permeability as well as the reduction and reorganizaion of TJ proteins. However, inhibiting autophagy with 3-methyladenine attenuated the burn-induced increase of intestinal permeability, as well as the reduction and reorganization TJ proteins. It is suggested that ER stress-autophagy axis contributes to the intestinal epithelial TJ barrier dysfunction after severe burn injury.